The Effectiveness of Using TED-Talk Video on Second Semester Students’ Speaking Skill in Speaking for Daily Communication Course at Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar - Ni Luh Tiamentari Pitri; I Dewa Gede Rat Dwiyana Putra; I Putu Andre Suhardiana (Indo Publishing, 2026)
This study aimed to examine the effectiveness of using TED-Talk video on second semester students’ speaking skill in Speaking for Daily Communication Course at Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar. This study used quasi-experimental design. The participants of this study were 38 students of second semester in English Language Education Department. The study used pre-test and post-test as instrument to collect the data. The data were analyzed by using descriptive statistical analysis and inferential statistical analysis through ANCOVA test. The post-test mean score of experimental group was higher (M = 91.43, SD = 4.057) compared to control group (M = 89.88, SD = 4.270). The ANCOVA result showed that there was significant difference in the post-test scores between experimental and control groups after controlling the pre-test scores, F (1,35) = 6.015, p = 0.019, ηp2 = 0.147. It can be concluded that there is significant effect os using TED-Talk on second semester students’ speaking skill in Speaking for Daily Communication course at Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar.